Astrocharis margarita sp. nov., a new snake star (Echinodermata, Ophiuroidea, Euryalidae) from a seamount in the Western Pacific - Xu, Rongrong; Xiao, Ning; Sha, Zhongli; Sun, Shaoe (Zootaxa, 2023)
During the scientific expedition of the R/V Kexue in 2014, a new species belonging to the genus Astrocharis Koehler, 1904 was collected from a seamount near the Yap Trench. Astrocharis margarita sp. nov. is distinguished from the other species of Astrocharis by the following characters: radial shields are partly naked or completely covered by polygonal ossicles, and the body color is uniformly light pink. Maximum Likelihood Tree and Bayesian Tree, based on a concatenated dataset of COI, 16S, and 18S genes analyses, indicated that the monophyly of Astrocharis was not supported, which suggested the genus needs to be revised.